Nano-Sized Cobalt Based Fischer-Tropsch Catalysts for Gas-to-Liquid Process Applications - Kang, Jung Shik; Awate, S. V.; Lee, Yun Ju; Kim, So Jung; Park, Moon Ju; Lee, Sang Deuk; Hong, Suk-In; Moon, Dong Ju (AMER SCIENTIFIC PUBLISHERS, 2010)
Nano-sized cobalt supported catalysts were prepared for Fischer-Tropsch synthesis in gas-to-liquid (GTL) process. The dependence of crystallite size and reducibility of Co3O4 on the supports were investigated with FTS activity. XRD peaks revealed nano crystallites (<5.47 nm) of Co3O4 crystallites. TEM showed round shaped particles with size less than 5 nm. Support with higher acidity decreased crystallite size Of Co3O4. XRD data of used catalysts showed Co3O4 crystallites smaller than 3.5 nm which do not reduce easily to Coo state. The crystallite size of Co3O4 plays a role in its reduction to Co-0. TPR results showed that the reduction temperature shifts to higher temperature due to metal-support interaction. The variation in the activity of the catalysts depends on the support which in turn affects the crystallite size, dispersion, reducibility and activity of Co species in Fischer-Tropsch Synthesis (FTS). In this study, Co/Al2O3 showed higher CO conversion than the other catalysts. However, the C5+ production was in order Co/SiO2 (78.1%) > Co/Al2O3 (70.0%) > Co/R_TiO2 (61 %) > Co/A_TiO2 (57.5%).